Alteration in CatSper1 and 2 genes expression, sperm parameters and testis histology in varicocelized rats - Maryam Zohour Soleimani; Farideh Jalali Mashayekhi; Morteza Mousavi Hasanzade; Maryam Baazm (Shahid Sadoughi University of Medical Sciences, 2018)
Background: CatSper gene, a member of cation channel sperm family, has an essential role in sperm motility and male fertility. Following varicocele, sperm parameters especially sperm movement decreases. For this reason, we hypothesized that CatSper gene expression might be reduced after varicocele induction in an animal model. Objective: The aim of this study was to evaluate the expression of CatSper 1 and 2 genes, sperm parameters and testis histology following varicocele induction. Materials and Methods: A total of 30 Wistar male rats were randomly divided into three following groups (n=10/ each): control, sham, and varicocele group. Experimental varicocele was induced by partial ligation of the left renal vein. The epididymal sperm parameters, CatSper1 and 2 genes expression, and testes histology were studied two months after varicocele induction. Results: Our results revealed that motility (32.73±16.14%), morphology (48.80±17%) and viability (31.23±9.82%) of sperms significantly reduced following varicocele induction. In addition, we showed a significant decrease in the number of spermatogonia (43.63±5.31) and seminiferous tubules diameters (190.51±19.23 mm) in experimental varicocele rats. The level of CatSper1 and 2 genes expression evaluated using real-time polymerase chain reaction was significantly downregulated 2 months after varicocele induction. Conclusion: Our data indicated that experimental varicocele has deleterious effects on sperm parameters, testis structure as well as the expression of CatSper 1 and 2 genes.